Methods of adapting preschool children to school education - Abdujabborova Zilola Ataulla qizi (Genius Journals, 2022)
This article examines the cooperation between the preschool education system and the school, as well as the methods and important areas of preparation of preschool children for school education. The tasks of preschool education and new aspects of teaching methods are discussed.
Keywords: Preschool; family; school; physical